Extending the π-conjugated molecules on TiO2 for the selective photocatalytic aerobic oxidation of sulfides triggered by visible light. Issue 7 (19th March 2021) - Li, Hui; Li, Xia; Lang, Xianjun
Abstract : The assembly of TiO2 surface with 1-hydroxy-2-naphthoic acid can give rise to an apparent red-shift of its absorption band, and subsequently engender the selective aerobic oxidation of sulfides triggered by visible light. Abstract : The assembly of TiO2 surface with π-conjugated molecules can give rise to an apparent red-shift of its optical absorption band, and subsequently engender ligand-to-metal charge transfer (LMCT) triggered by visible light. However, the application of LMCT remains elusive due to the vulnerability of these π-conjugated molecules at the vicinity of reactive centers. Therefore, extending the π-conjugation of these molecules could be envisioned to overcome this bottleneck with the oxidation of sulfides as a probe reaction. With salicylic acid (SA) as the starting molecule, extending the benzene ring at 5, 6 or 3, 4 positions with another one afforded 2-hydroxy-1-naphthoic acid (2H1NA) and 1-hydroxy-2-naphthoic acid (1H2NA). Compared to SA, 2H1NA showed a moderate improvement, while 1H2NA caused a significant enhancement for modifying anatase TiO2 to conduct the selective aerobic oxidation of sulfides triggered by blue light with (2, 2, 6, 6-tetramethylpiperidin-1-yl)oxyl (TEMPO) as a redox mediator. Ultimately, the aerobic oxidation of organic sulfides to corresponding sulfoxides in CH3 OH could be achieved by the 1H2NA–TiO2 photocatalyst in cooperation with TEMPO. This study introduces the assembly of extended π-conjugated molecules on TiO2, which may pave the way to construct more efficient visible-light photocatalysts.